The Role of Parenting Styles in Internalizing Islamic Moderation Values in Children: A Phenomenological Study - Hamdun, Dudung (Jurnal Pendidikan Islam, 2022)
Purpose – This qualitative study investigates the pivotal role of parents in the internalization of Islamic moderation values in child development, as well as the determinants of parental behavior, knowledge, and practices. Additionally, the research identifies implications for further studies and practical applications. Design/methodology/approach – The phenomenological methodology is employed to comprehend and describe these phenomena, delving into the essence of parents' experiences. Findings – The results demonstrate that parents are responsible for shaping children's behavior and instilling Islamic moderation values. Factors such as parental experience and education, profound understanding, quality aspects, and parenting methods by exemplary parents serve as determinants of parental behavior, knowledge, and practices in incorporating Islamic moderation values in child development. Overall, the findings suggest that among all modifiable factors influencing a child's development, the quality of care children receive is of utmost importance, warranting further academic investigation. Research implications/limitations – The study emphasizes the role of parents in the internalization of Islamic moderation values; however, it does not examine the long-term effects of such internalization on children's overall development and well-being. Practical implications – This research offers valuable insights for practitioners, highlighting that parenting, when carried out effectively, can be a highly fulfilling role, bringing immense joy, pride, and happiness to a parent's life.